Staphylococcus epidermidis Sensitizes Perinatal Hypoxic-Ischemic Brain Injury in Male but Not Female Mice - Gravina, Giacomo (Front Immunol, 2020)
Background: Staphylococcus epidermidis is the most common nosocomial infection and the predominant pathogen in late-onset sepsis in preterm infants. Infection and inflammation are linked to neurological and developmental sequelae and bacterial infections increase the vulnerability of the brain to hypoxia-ischemia (HI). We thus tested the hypothesis that S. epidermidis exacerbates HI neuropathology in neonatal mice. Methods: Male and female C57Bl/6 mice were injected intraperitoneally with sterile saline or 3.5 × 10(7) colony-forming units of S. epidermidis on postnatal day (PND) 4 and then subjected to HI on PND5 (24 h after injection) or PND9 (5 d after injection) by left carotid artery ligation and exposure to 10% O(2). White and gray matter injury was assessed on PND14-16. In an additional group of animals, the plasma, brain, and liver were collected on PND5 or PND9 after infection to evaluate cytokine and chemokine profiles, C5a levels and C5 signaling. Results: HI induced 24 h after injection of S. epidermidis resulted in greater gray and white matter injury compared to saline injected controls in males, but not in females. Specifically, males demonstrated increased gray matter injury in the cortex and striatum, and white matter loss in the subcortical region, hippocampal fimbria and striatum. In contrast, there was no potentiation of brain injury when HI occurred 5 d after infection in either sex. In the plasma, S. epidermidis-injected mice demonstrated increased levels of pro- and anti-inflammatory cytokines and chemokines and a reduction of C5a at 24 h, but not 5 d after infection. Brain CCL2 levels were increased in both sexes 24 h after infection, but increased only in males at 5 d post infection. Conclusion: Ongoing S. epidermidis infection combined with neonatal HI increases the vulnerability of the developing brain in male but not in female mice. These sex-dependent effects were to a large extent independent of expression of systemic cytokines or brain CCL2 expression. Overall, we provide new insights into how systemic S. epidermidis infection affects the developing brain and show that the time interval between infection and HI is a critical sensitizing factor in males.